CRITICAL LEGAL STUDIES (CLS): AN ALTERNATIVE FOR CRITICAL LEGAL THINKING IN INDONESIA - Muchamad Ali Safa’at; Milda Istiqomah (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2022)
This article discusses Critical Legal Studies (CLS) as the critical study of the law that opposes the doctrine of legal formalism. As a form of critical study, CLS accommodates not only Marxist legal ideas but also liberalist-radical and postmodernist ones. This article aims to describe the ideas contained within CLS from the perspectives of various legal experts and identify its advantages and disadvantages, as well as its context with the legal development in Indonesia. The normative research method was utilized for the investigation and analysis of the existing legal doctrines. This article concludes with a critique of the law in Indonesia at present and an explanation as to how the ideas of CLS may be utilized as another radical alternative for solving legal problems in Indonesia. Abstrak: Artikel ini membahas mengenai Critical Legal Studies (CLS) sebagai studi kritis hukum yang menentang doktrin formalisme hukum. Sebagai bentuk kajian kritis, CLS tidak hanya menampung ide-ide hukum Marxis, tetapi juga liberalis-radikal dan postmodernis. Artikel ini bertujuan untuk mengidentifikasi secara singkat gagasan-gagasan yang terkandung dalam CLS dari berbagai pakar hukum, kelebihan dan kekurangannya, serta konteksnya dengan perkembangan hukum di Indonesia. Metode penelitian yang digunakan adalah metode normatif untuk mengkaji dan menganalisis keberadaan doktrin-doktrin hukum. Artikel ini diakhiri dengan kritik terhadap hukum di Indonesia saat ini dan bagaimana gagasan CLS dapat dimanfaatkan sebagai alternatif radikal lain dalam menyelesaikan permasalahan hukum di Indonesia.Kata Kunci: Studi Kritis Hukum, Doktrin Formalisme Hukum, Alternatif Radikal.